Auto-anthological pathways of Diego Valeri (Configurazioni. Research on contemporary poetry, 2023)
Diego Valeri (1887-1976) published some self-anthologies: Poesie vecchie e nuove (1930, 1952), Terzo tempo (1950). With Poesie (1962) Valeri brings out a book with unpublished texts and peritexts. In 1967 Poesie was transformed with the expunction of texts or the addition of new ones. Valeri died on November 27th, 1976: he was personally attending to the Poesie scelte (January 1977, edited by Carlo Della Corte). The speech reveals the reasons and strategies of Valeri anthologist and will close on the annotations of the writer, editor of the first non-authorial sylloge of Valerian poetry.
Keywords: Diego Valeri; Vittorio Sereni; XXth Century Poetry; Anthologies; Italian Poetry